2009
DOI: 10.1007/s10029-009-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated inguinal hernia: atypical presentation of an abdominal aortic aneurysm

Abstract: The diagnosis of an inguinal hernia, be it complicated or uncomplicated, is often simple and straight forward. Rarely, this simple presentation may be the external manifestation of a distant pathology, which is in communication with the inguinal canal through its anatomic relationship. We report a case of ruptured abdominal aortic aneurysm (AAA) that presented as a strangulated left inguinal hernia. To the best of our knowledge, this is the first reported case where the patient was stable on initial presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Rarely, RAAA can mimic incarcerated inguinal hernia, typically presenting as painful lump in the groin [7] . Literature search reveals in total 18 patients with ruptured aortoiliac aneurysms initially presenting as symptomatic/incarcerated hernia [2] , [3] , [4] , [8] , [9] , [10] , [11] , [12] . The fact that rupture of abdominal aneurysm appears as symptomatic hernia should not be surprising: First, there is increased activity of matrix metalloproteinases and their inhibitors in both abdominal wall (responsible for weakness of abdominal wall with subsequent hernia) and aortic walls (responsible for weakness of aortic wall and subsequent aneurysm formation) [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, RAAA can mimic incarcerated inguinal hernia, typically presenting as painful lump in the groin [7] . Literature search reveals in total 18 patients with ruptured aortoiliac aneurysms initially presenting as symptomatic/incarcerated hernia [2] , [3] , [4] , [8] , [9] , [10] , [11] , [12] . The fact that rupture of abdominal aneurysm appears as symptomatic hernia should not be surprising: First, there is increased activity of matrix metalloproteinases and their inhibitors in both abdominal wall (responsible for weakness of abdominal wall with subsequent hernia) and aortic walls (responsible for weakness of aortic wall and subsequent aneurysm formation) [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Both cases finally turned out to be RAAA. This atypical presentation often undergoes erroneous preoperative management which frequently delays surgical treatment resulting in poor survival [10] . Thus we suggest, that patients with suspected symptomatic inguinal hernia combined with hypotension (leading to collapse) or the presence of blood in the spermatic cord while surgical hernia repair should immediately receive thoracoabdominal CTA for both diagnosing the RAAA and optimal preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…6 Further case series have shown that patients have been taken for surgery based on an incorrect diagnosis. 7,8 Cases of retroperitoneal haematomas presenting as an incarcerated hernia are also documented, again with inappropriate operations being performed.…”
Section: Case Historymentioning
confidence: 99%